Scientific Article: The Strategic Role of the Indonesian National Police (Polri) in Empowering the Three Pillars of the State for National Security and Public Order Stability (Kamtibmas) - R. Nurcahyo Aji; Nani Nurani Musin; Rahmat Salam (Journal Of Social Science (JoSS), 2025)
This study analyzes in depth the strategic role of the National Police of the Republic of Indonesia (Polri) in empowering the three pillars of the state as a vital instrument to achieve National Security and Public Order (Kamtibmas) stability. Domestic political dynamics show high complexity, exacerbated by fluctuations in public participation that indicate a crisis of trust and potential social conflict. The National Police is positioned not only as a law enforcement actor but also as a political communication actor that functions as a mediator of the articulation of public interests and government policies. This qualitative research focuses on the effectiveness of the state tripillar synergy between the Executive, Legislature, and Judiciary, with an emphasis on the role of facilitation and education by the National Police. Specifically, this study finds that: the National Police's digital communication platforms reached over 170 million users but face credibility challenges due to past human rights violations; the mediation role of the Police in Musrenbang forums successfully bridged community-government communication gaps;  legislative facilitation programs enhanced public access to the legislative process; and legal education initiatives by the Police improved community understanding of judicial procedures by enabling better access to justice. The results show that the integration of Political Communication Theory, Responsive Government Theory, and Community Policing Theory is absolutely necessary. The success of the National Police in utilizing digital platforms and dialogue forums will be decisive in building social trust and creating deliberative governance, which in turn is a prerequisite for achieving sustainable Kamtibmas.